(untitled) (Annals of Medical Research, 2024)
Aim: Forensic medicine is one of the basic areas of duty and responsibility of physicians just like the preventative, diagnostic, and treatment services of medicine. The aim of this study was to emphasise the importance of practice-based theoretical forensic medicine education by evaluating students who had taken and not taken forensic medicine internship. Materials and Methods: Two groups were formed of students who had taken and not taken practice-based forensic medicine internship. A questionnaire of 24 items was administered to the students to evaluate their level of knowledge related to forensic medicine and expertise. The data obtained were analyzed statistically using SPSS vn. 24 software (IBM SPSS, Somers, NY, USA). Results: There were seen to be statistically significant differences between the groups in the responses to many of the questions. Students who had not taken a forensic medicine internship felt that their knowledge was lacking on subjects related to forensic medicine, and the results showed deficiencies in these subjects. Conclusion: Consistent with findings in literature, students who had not taken a forensic medicine internship felt inadequate in areas related to forensic medicine services and it was seen that their knowledge related to these subjects was lacking. Forensic medicine education should be an integral part of the medical faculty syllabus.